Islamic Education in Middle School Perspective KH. Ahmad Dahlan (1868 – 1923 M) - Nur Azizah Lubis; Mhd Rasid Hamdi; Hakmi Wahyudi; Zulfadhly Mukhtar (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Islamic Renewal Thought is a very interesting study in the development of thought in the Islamic world. Moreover, the emergence and renewal movements that occurred in Indonesia provided a new, more advanced atmosphere in the field of Islamic Education. K.H. Ahmad Dahlan is a reformist thinker in Indonesia who is engaged in education. Ahmad Dahlan sees that the problem of education is the main root that causes the Indonesian nation, especially Muslims to be left behind. That's why he took the educational path as the main means of preaching. However, to expand the movement of this da'wah step, the existence of educational institutions is presumably too narrow. Some of Ahmad Dahlan's friends advised him to establish an organization. Finally he founded the Muhammadiyah organization. One of the Muslim intellectuals or Islamic education figures who tried to reconstruct the paradigm building that could be used as the basis for the National Education system was KH Ahmad Dahlan. He is a reformist figure in Indonesia who comes with his thoughts to respond to the condition of the ummah, especially in the field of Islamic education, which was very bad in Indonesia during the Dutch colonial government. Seeing this with the K.H. renewal movement. Ahmad Dahlan struggled to change education for the better and more advanced. KH.Ahmad Dahlan is called to take part in thinking about and improving the plight of Indonesian Muslims. KH.Ahmad Dahlan's efforts were realized with the establishment of the Muhammadiyah Organization. The purpose of writing this article is to find out K.H. Ahmad Dahlan on Renewing Islamic Education in Indonesia. The method used is qualitative with the approach used is library research where the data is obtained through various existing literacy.